Analysis of Soot Particle Movement in Diesel Engine under the Influence of Drag Force - Mohd Hafidzal, Mohd Hanafi; Roslizar, Aiman; Zakaria, Mohamad Shukri; Saadun, Mohd Noor Asril; Saleman, Abd Rafeq (Trans Tech PublicationsApplied, 2013)
The formation of soot is influenced by the composition of air entrainment and structure of hydrocarbon in the fuel. Soot will then form during combustion in a diesel engine. Some of the soot particles will be released from the engine through the exhaust nozzle and some will stick to the cylinder walls. The soot that sticks to the cylinder wall can affect the lifetime of the lubricant oil. Subsequently this will decrease the durability of the diesel engine. By understanding the movement of the soot particles, the effect to the engine can be decreased. Therefore, the initial position and last position of soot particle was recognized through this study. The data for the formation of soot particles in the diesel engine was obtained from previous investigation. The study of soot movement at 8° crankshaft angle under the influence of drag force with different radial, axial and angular settings were carried out using a MATLAB routine. The results showed that the movement of soot particle will change with different parameter settings. Besides that, comparison of the results of soot particle movement influenced by drag force and without drag force has been carried out. It was observed that drag force caused shorter soot particle movement path and moves them away from the cylinder wall.